The Effect of Transfers and Position Promotions on Employee Performance, Study of PT Dazzle Yogyakarta Employees - Trio Aprialdi Syahputra (Proceeding of The International Conference on Economics and Business, 2022)
The problem in this study is related to the performance of PT Dazzle Yogyakarta employees affected by mutations and promotions. This research is motivated by the implementation of mutations that are carried out erratically and promotions only apply to full-time employees at PT Dazzle Yogyakarta. This research aims to: 1). Knowing the effect of mutation on the performance of employees of PT Dazzle Yogyakarta, 2). To determine the effect of promotion on the performance of employees of PT Dazzle Yogyakata, 3). To determine the effect of mutations and promotions on the performance of employees of PT Dazzle Yogyakarta.This type of research uses quantitative methods with primary data types obtained from distributing questionnaires with a Likert scale and processed with SPSS version 26 through hypothesis testing. In this study using 65 respondents. The tools used are quantitative analysis using data quality tests, classical assumption tests, multiple linear regression analysis and hypothesis testing using t-tests and F-tests. The research results show: 1). Mutations on the performance of employees of PT Dazzle Yogyakarta have a significant effect, 2). Promotion of position on the performance of employees of PT Dazzle Yogyakarta has a significant effect, 3). Transfers and promotions on the performance of employees of PT Dazzle Yogyakarta have a significant effect.